PEPTIDE RECEPTOR RADIONUCLIDE THERAPY - Hidayatullah, Rian; Budiawan, Hendra; Darmawan, Budi; Affandi, Erwin (Faculty of Medicine Universitas Mataram, 2021)
Peptide receptor radionuclide therapy (PRRT) is an effective and usually well-tolerated treatment for unresectable or metastatic neuroendocrine tumors expressing somatostatin receptors. Somatostatin analog which is labeled by ?- or ?-emitting radionuclide binds specifically to SSTRs abnormally expressed in NETs. The two radiopharmaceuticals most commonly used for PRRT are 90Y-DOTATOC and 177Lu-DOTATATE which have been demonstrated to provide an effective tumor response and symptom relief with positive impact on survival. Chronic side effects on the kidneys and bone marrow are generally mild. The radiopharmaceuticals is internalized into the cell for the irradiation. Furthermore, the long half-life of the analog maintains a persistent therapeutic effect. Different approaches are now under evaluation to improve PRRT efficacy, it may be expected that the use of PRRT will increase in the coming years.